Pengaruh Latihan Fisik terhadap Perbaikan Resistensi Insulin - Devitya Angielevi Sukarno (Direktorat Penerbitan dan Publikasi Ilmiah Universitas Surabaya, 2021)
Abstract--Insulin resistance underlies the pathogenesis of chronic disease, such as diabetes mellitus which has high morbidity and mortality rate. Insulin resistance is a pathological condition when cells fail to respond normally to the insulin hormone, because of insulin signaling pathway disruption. Bound between insulin and insulin’s receptor cannot phosphorylate tyrosine and fail to activate insulin receptor substrate-1 (IRS-1). This failure decrease Glucose transporter-4 (GLUT-4) expression on the skeletal muscle’s cell membrane, that leads to decrease glucose influx and increase blood glucose level. A routine physical training which does according to adequate training dose, will activate adenosin 5’monophosphate-activated protein kinase (AMPK) and lead to the translocation of GLUT-4 vesicles without insulin and insulin’s receptor bonding.GLUT-4 expression on the skeletal muscle’s cell membrane which is stimulated by muscle contraction will increase glucose influx and decrease blood glucose level.